2019
DOI: 10.1016/j.jsr.2019.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Safer than the average human driver (who is less safe than me)? Examining a popular safety benchmark for self-driving cars

Abstract: Although the level of safety required before drivers will accept self-driving cars is not clear, the criterion of being safer than a human driver has become pervasive in the discourse on vehicle automation. This criterion actually means "safer than the average human driver," because it is necessarily defined with respect to population-level data. At the level of individual risk assessment, a body of research has shown that most drivers perceive themselves to be safer than the average driver (the better-than-av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…However, this explanation is refuted by our post-assessment questions which found participants expressing higher likelihood of making a mistake (in the considered situations) for machine drivers than for human drivers. This runs counter to the literature on the public's risk acceptance of AVs, which shows that the public expects AVs to be significantly safer than human drivers, feel reasonably safe riding in an AV, and would allow AVs on public roads ( Nees, 2019 ). Our participants' expectation of failure can be seen as an expectation of a driver's ability to avoid a mistake i.e., higher perceived competence at driving for humans.…”
Section: Discussioncontrasting
confidence: 63%
“…However, this explanation is refuted by our post-assessment questions which found participants expressing higher likelihood of making a mistake (in the considered situations) for machine drivers than for human drivers. This runs counter to the literature on the public's risk acceptance of AVs, which shows that the public expects AVs to be significantly safer than human drivers, feel reasonably safe riding in an AV, and would allow AVs on public roads ( Nees, 2019 ). Our participants' expectation of failure can be seen as an expectation of a driver's ability to avoid a mistake i.e., higher perceived competence at driving for humans.…”
Section: Discussioncontrasting
confidence: 63%
“…Many of them concentrate on demographic factors. It has been confirmed that younger male drivers had a more positive attitude towards AVs and were more willing to buy one [23,[34][35][36][37]. Moreover, such factors like higher income [35], living in an urban area [38], techsavvy and also involvement in more crashes [39] positively affect the attitudes towards AVs [13].…”
Section: Acceptance Of Autonomous Vehiclesmentioning
confidence: 84%
“…As mentioned earlier, ACs use a number of cameras, sensors, radars, communication devices, protocols and algorithms to safely manoeuvre in traffic. Due to the several media covered accidents which involved test ACs, as well as to the human's general distrust of new technologies, concerns regarding the safety of ACs are high [7][8][9] and most drivers think that the level of automation which is thought to be safer than a human driver will not represent an acceptably safe performance for most drivers [26].…”
Section: Figurementioning
confidence: 99%